Quality evaluation and functional properties of Kokoro produced from maize and African yam bean flour blends (Agriculture, Food, and Natural Resources Journal, 2025)
This study was conducted to evaluate the nutritional composition of “Kokoro” produced from maize (M) and African yam bean (AYB) composite flour. Different ratios of M and AYB composite flour were formulated, ranging from Sample XWB: 100% maize flour; YVA: 95% maize flour and 5% AYB; KRM: 90% maize flour and 10% AYB; Sample PND: 85% maize flour and 15% B; and GSZ: 80% maize flour and 20% AYB. The flour and maize chips' proximate and mineral compositions were evaluated. Sensory characteristics of the maize chip were determined. The result obtained for proximate composition of flour and maize chip (M and AYB composite flour) showed a mean moisture content of 9.96% and 13.52%, crude protein of 3.13% and 0.86%, crude fat of 2.84% and 8.99%, crude fiber of 1.18% and 1.42%, total ash of 2.05% and 2.00%, and carbohydrate of 77.27% and 74.17%, respectively. The mineral composition of the maize chips contained a mean calcium of 54.00 mg/100g, magnesium of 13.75 mg/100g, iron of 2.80 mg/100g, sodium of 82.50 mg/100g, zinc of 0.01 mg/100g, and phosphorus of 33.75 mg/100g. The study showed that the nutritional quality of maize chips can be improved through the addition of AYB. This is reflected in the improved nutrition, which increased with the increase in AYB flour inclusion level. The substitution of maize with AYB significantly improved the mineral and functional properties of the blends. Sensory evaluation showed that consumers tend to prefer maize chips from 90:10 M and AYB composite flour.
Keywords: African yam bean; Flour blends; Maize; Maize-chip